2016
DOI: 10.1007/s00221-016-4654-0
|View full text |Cite
|
Sign up to set email alerts
|

The visual representations of motion and of gravity are functionally independent: Evidence of a differential effect of smooth pursuit eye movements

Abstract: The memory for the final position of a moving object which suddenly disappears has been found to be displaced forward, in the direction of motion, and downwards, in the direction of gravity. These phenomena were coined, respectively, Representational Momentum and Representational Gravity. Although both these and similar effects have been systematically linked with the functioning of internal representations of physical variables (e.g. momentum and gravity), serious doubts have been raised for a cognitively bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Hence, if a stimulus moves, it would be reasonable for the sensory system to predict the next sensory input in the direction of anticipated motion. In line with such a suggestion, Berry and colleagues (1999) found an anticipation effect for visual stimuli moving across the retina (see De sá Teixeira, 2016;Hubbard, 2005Hubbard, , 2014Kerzel, 2000, for discussion concerni ng the i nfl uence of eye m ovements on representational momentum). Interestingly, most theories of representational momentum consider this effect to be modality-independent (see Hubbard, 2010).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hence, if a stimulus moves, it would be reasonable for the sensory system to predict the next sensory input in the direction of anticipated motion. In line with such a suggestion, Berry and colleagues (1999) found an anticipation effect for visual stimuli moving across the retina (see De sá Teixeira, 2016;Hubbard, 2005Hubbard, , 2014Kerzel, 2000, for discussion concerni ng the i nfl uence of eye m ovements on representational momentum). Interestingly, most theories of representational momentum consider this effect to be modality-independent (see Hubbard, 2010).…”
Section: Introductionmentioning
confidence: 85%
“…In the horizontal plane, most studies have not reported any difference between left-and rightward movement (Cooper & Munger, 1993;Hubbard, 1990Hubbard, , 1995aHubbard & Bharucha, 1988; but see Halpern & Kelly, 1993). In the vertical plane, downward movement/ descending stimuli tend to elicit stronger forward shifts than upward m ovement/ascending stimul i, known as representational gravity (e.g., De sá Teixeira, 2016;De sá Teixeira, Hecht, & Oliveira, 2013;Hubbard, 1990Hubbard, , 1995bHubbard, , 2005. For stimuli that move in the depth plane, a forward shift has been evidenced, yet consistent differences between approaching and receding events have not been reported.…”
Section: Localization Of Dynamic Tactile Stimuli: Influence Of Directmentioning
confidence: 99%
“…Importantly enough, and although eye movements were found to follow a course similar to the behavioural findings when left unconstrained (Experiment 2), the pattern of spatial mislocalization did not change when observers were forced to keep their gaze steady (Experiments 3a and 3b). These results have been interpreted as resulting from an internal model of gravity that modulates the spatial updating in memory of the remembered vanishing location (De Sá Teixeira, 2016b;De Sá Teixeira & Oliveira, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…To start with, one should notice that any spatial localization error of a moving target is determined by two independent phenomena (see De Sá Teixeira, 2014, 2016bDe Sá Teixeira & Hecht, 2014;Motes, Hubbard, Courtney, & Rypma, 2008), each linked with its own reference direction. On the one hand, representational momentum, predicting an error forward, should depend solely on the target's motion direction.…”
Section: The Measurement Of Mnesic Spatial Displacements Through Fourmentioning
confidence: 99%
“…Since the beginning of time, all living organisms have evolved under a constant terrestrial gravitational field of approximately 9.81 m/s 2 , known as 1 g. On Earth, gravity is always there; it is therefore not surprising that the physical constraints of Earth’s gravity are internalised in the human brain to shape our perception and action (Indovina et al 2005 ). For instance, random accelerations are hardly perceived at all (Werkhoven et al 1992 ), falling objects are expected to accelerate even when their velocity is constant (Zago et al 2004 ), and observers misremember the location of moving objects in space (De Sá Teixeira 2016 ). In addition, gravity can influence eye movements, with improved smooth pursuit of objects which move according to 1 g vs objects which move according to weightlessness (0 g), reversed gravity (− 1 g), or hypergravity (2 g) (Delle Monache et al 2015 ; Jörges and López-Moliner 2019 ).…”
Section: Introductionmentioning
confidence: 99%